On ABC4 and GA5 Index of Subdivided and Line Graph of Subdivided Dutch Windmill Graph - Iqbal, Hifza (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
Topological indices are the numeric descriptors of a graph which characterizes its topology and it is structure invariant. Topological indices introduced on the molecular structure can help material scientists to understand its chemical and biological features in better and easy way [2, 11, 13 14, 16]. In this pa- per, we present neighborhood based topological indices of sub-divided Dutch windmill graph and line graph of subdivided Dutch windmill graph.